CYBERPORN PROTECTION AGAINST EARLY CHILDHOOD - Munisa, Munisa; Tasril, Virdyra; Syahira, Wardah (Proceeding International Conference of Science Technology and Social Humanities, 2022)
The rapid development of technology in Indonesia has an effect on people's social life and security. The high penetration of internet users opens up its own opportunities for the emergence of cyberspace-based crime crimes. Children are more at risk of becoming victims of crimes in cyberspace, one of which is the crime of pornography. The spread of Cyberporn over the internet is said to be cheaper, easier, and safer from raids, compared to pornographic content through print media and other film industries that are prone to raids. This convenience allows anyone to access it anytime, anywhere and without anyone knowing, including early childhood. Parents have the task of supervising or controlling (parental control) of internet use for their children, especially during the previous pandemic, children have familiarized their use of the internet with learning needs and so on. This study aims at the extent of understanding parents and schools in knowing the negative impacts of pornography exposure and knowing how to eradicate how to block, deter, and eradicate cyberporn through the use of Add Ons.